Hematopoietic stem cell gene therapy ameliorates CNS involvement in murine model of GM1-gangliosidosis - Toshiki Tsunogai; Toya Ohashi; Yohta Shimada; Takashi Higuchi; Ayaka Kimura; Ayako M. Watabe; Fusao Kato; Hiroyuki Ida; Hiroshi Kobayashi (Molecular Therapy: Methods & Clinical Development, 2022)
GM1-gangliosidosis is a progressive neurodegenerative glycosphingolipidosis resulting from a GLB1 gene mutation causing a deficiency of the lysosomal enzyme β-galactosidase, which leads to the abnormal accumulation of GM1 ganglioside in the central nervous system. In the most severe early infantile phenotype, excessive ganglioside accumulation results in a rapid decline in neurological and psychomotor functions, and death occurs within 2 years of age. Currently, there is no effective therapy for GM1-gangliosidosis. In this study, we evaluated the therapeutic efficacy of ex vivo gene therapy targeting hematopoietic stem cells using a lentiviral vector to increase enzyme activity, reduce substrate accumulation, and improve astrocytosis and motor function. Transplanting GLB1-transduced hematopoietic stem cells in mice increased β-galactosidase enzyme activity in the central nervous system and visceral organs. Specifically, this gene therapy significantly decreased GM1 ganglioside levels in the brain, especially in the cerebrum. More important, this gene therapy rectified astrocytosis in the cerebrum and improved motor function deficits. Furthermore, the elevation of serum β-galactosidase activity in secondary-transplanted mice suggested the ability of transduced hematopoietic stem cells to repopulate long term. These data indicate that ex vivo gene therapy with lentiviral vectors is a promising approach for the treatment of brain deficits in GM1 gangliosidosis.